An updating technique for finite elements models of existing high-rise buildings through ambient vibration tests - Villanueva, Luis I.
An enhanced procedure that integrates ambient vibration (AV) test and finite clement (FE) analysis results to improve the analytical model of existing high-rise buildings is developed. The natural frequencies and corresponding mode shapes derived from AV measurements are used as basis for updating the FE model of existing buildings. The basic idea is that these modal parameters are functions of the physical properties of the structures, hence can provide information about the "health" of the structure in-situ. A case study on an existing 12- story reinforced concrete (RC) building id conducted to assess the procedure developed. To illustrate the logistical constraints in practical situations, only five (5) vibration sensors are allocated.
The Reference-based Stochastic Subspace Identification (SSI/Ref) technique is used to identify the modal parameters of interest from the AV measurements. The technique requires specifying parameters for data processing. Stability analysis is performed to establish the optimum parameters for AV data processing using SSI/Ref, in such a way that gross errors are ruled out.
Meanwhile, the analytical model of the building is created adopting the FE codes of STRAND7 ver. 1.06.5 software. The initial FE model, which is based on the available structural drawing and limited geometric survey, is constructed to determine the analytical natural frequencies and mode shapes of the test structure.
A direct comparison between the experimentally identified modal parameters and the analytical predictions is made. The mode shape information are used to pair the modes correctly. The degree of correlation between the FE model and the test data using mode shapes is quantified through the Modal Assurance Criterion (MAC). Differences between the experimentally identified and analytically identified natural frequencies are used as basis for the updating study.
To bring the two sets of modal data closer together, refinements on the model features and adjustments of model parameters are performed. To distinguish the improvements made on the FE model, the categories of a, b, and y Model are introduced. A and B Models are subjected to updating to achieve the Y Model.
The procedure adopts the "indirect" method of model updating. The indirect updating process is further categorized in this study into two stages, Global Updating and Local Updating. Global updating involves wholesale variation of model parameters, while local updating involves variation of elemental or member properties at specific areas or locations in the building or structure.
In the case study, global and local updates on stiffness-related parameters, E and I, of select structural members are needed to bring more closely the analytical natural frequencies with that of the AVT. The results of the sensitivity analysis are used in the process. To account for small errors inherent in the test, a+/-10% margin of difference is considered as acceptable limit.
The results of the model updating study show that development of accurate analytical model of large civil structures can be practically accomplished with the use of limited AV test data. Furthermore, updating can be performed at local level(s), that is, at specific areas or locations (e.g. floor level) in the building or structure. For RC buildings, the uncertainties of stiffness-related parameters E and I are considered for updating. Mass-related parameters such as p, on the other hand, have less allowance for variations.
Mode shape information can also be used to detect localized deviations. However, the limited measurements of the present application have inhibited to make use of this modal parameter, except in the modal pairing.
"November 2004."
Thesis (M.S. Civil Engineering) -- University of the Philippines, Diliman.
Keywords: Tall buildings -- Vibration -- Philippines -- Manila Metropolita Area; Structural analysis (Engineering).; Structural dynamics